Report on Visitation by National Council for Higher Education (NCHE) Inspection of Health Sciences Finalists and E-Learning (ODEL) Readiness - Kabale University (Kabale University, 2023)
National Council for Higher Education visited the University purposely for inspection of two things; readiness for re-opening for finalists of health sciences in the medical school and e-learning preparedness. This visitation occurred as a response to the request by the Vice Chancellor in her letter dated 23rd September 2020 to NCHE to come for inspection and clearance for students’ teaching and learning. In the same meeting, Kabale University School of Medicine (KABSOM) and e-learning Team gave presentations on COVID -19 preparedness and ODeL Model readiness respectively. After presentations, NCHE Team went for a tour around KABSOM main building (where the meeting took place) and, ICT department (Computer Laboratories) guided by Vice Chancellor and Deputy Academic Registrar to inspect facilities that were put in place in preparation for re-opening of finalist students.